2‐Acetamido‐2‐deoxy‐l‐iminosugar C‐Alkyl and C‐Aryl Glycosides: Synthesis and Glycosidase Inhibition. Issue 40 (14th August 2018) - Fontelle, Nathalie; Yamamoto, Arisa; Arda, Ana; Jiménez‐Barbero, Jesús; Kato, Atsushi; Désiré, Jérôme; Blériot, Yves
Abstract : The synthesis of a series of six‐membered 2‐acetamidol ‐iminosugar C ‐alkyl and C ‐aryl glycosides is reported. A diastereoselective sugar‐ring enlargement/ C ‐alkylation (or arylation) /ring‐contraction sequence applied tod ‐ gluco ‐ andd ‐ manno ‐configured 2‐acetamido azidolactols provides newl ‐iminosugar C ‐glycosides. The 1, 2‐ trans stereocontrolled introduction of the pseudoanomeric substituent in these heterocycles strongly suggests a NHAc neighbouring‐group participation. In their deprotected form, the nine iminosugars exhibit moderate hexosaminidases and β‐glucuronidase inhibition. Abstract : A Staudinger/azawittig/Grignard/ring‐contraction sequence applied to twod ‐glycopyranose derivatives bearing an acetamido group at the C‐2 position and an azido group at the C‐6 position allows access to unprecedented six‐memberedl ‐iminosugars C ‐glycosides as GlcNAc and ManNAc mimics. The high 1, 2‐ trans diastereoselectivity observed for the Grignard addition strongly suggests an anchimeric assistance by the NHAc group.